Accessibility by public transport for older adults: A systematic review. (July 2022) - Ravensbergen, Léa; Van Liefferinge, Mathilde; Isabella, Jimenez; Merrina, Zhang; El-Geneidy, Ahmed
Abstract: Accessibility, the ease of reaching destinations through a transport network, holds great potential to help foster equitable and sustainable cities. Though equity analyses are often considered in accessibility studies, only recently have researchers begun to consider older adults' access to destinations. In the context of an aging population, this paper presents a systematic review of the literature on older adults' accessibility using public transport. Our comprehensive review identifies articles focused on older adults' access to destinations via public transport published since 2000 ( n = 16). Quality assessments indicate that this work has little risk of selection bias but could improve when it comes to study design. The ways in which accessibility are measured vary greatly across papers, with regards not just to accessibility metrics, but also the type of destinations used, public transport modes considered, and the ways in which older people are conceptualized. This makes it difficult to draw conclusions across studies on older adults' accessibility. Therefore, we call for more research on older adults' accessibility that engages with critical gerontology and age-friendly city frameworks. Doing so should involve centering the voices and experiences of older people into public transport accessibility research by, for instance, asking them which destinations should be considered and which thresholds should be used. In practice, this can be achieved through an experience-based co-design research approach or by actively reaching out to older people through other methods such as surveys, interviews, or focus groups.